Rethinking Multicultural Resilience through Digging4Data and Heritage-Based Infill Design: The Case of Peunayong Market District, Banda Aceh - Muhammad Naufal Fadhil; Aji Sofiana Putri (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2026)
The Peunayong market district in Banda Aceh presents a critical urban paradox: an organic, multicultural heritage marketplace operating since the seventeenth century that currently contrasts with contemporary governance metrics that designate Banda Aceh as an intolerant city. This study examines how architectural history research, when integrated with adaptive infill design, can address the district's socio-spatial fragmentation caused by recent market relocations (2019) and heritage vandalism (2025). Employing the Digging4Data methodology, this study draws on historical cartography and photography, spatial documentation of eight heritage sites, and structured interviews with 6 key informants, including local community leaders and long-term vendors, to identify the historical mechanisms that sustain multicultural resilience in Peunayong. The analysis reveals three enduring resilience factors: (1) modular spatial configurations, (2) robust cross-ethnic merchant networks, and (3) persistent material cultural symbols. Based on these findings, eight context-responsive infill design prototypes are proposed and directly validated through participatory focus group discussions to ensure alignment with contemporary community needs. This study argues that multicultural identity is a dynamic, living heritage asset. The main scholarly contribution is an evidence-based framework for integrating heritage conservation into post-disaster urban recovery, demonstrating that sustainable revitalization requires participatory spatial design and policy mechanisms that prioritize community-generated resilience over centralized displacement.